Sedimentary record and anthropogenic pollution of a complex, multiple source fed dam reservoirs: An example from the Nové Mlýny reservoir, Czech Republic - Sedláček, Jan; Bábek, Ondřej; Nováková, Tereza (The Science of the total environment, 2017)
While numerous studies of dam reservoirs contamination are reported world-wide, we present a missing link in the study of reservoirs sourced from multiple river catchments. In such reservoirs, different point sources of contaminants and variable composition of their sedimentary matrices add to extremely complex geochemical patterns. We studied a unique, step-wise filled Nové Mlýny dam reservoir, Czech Republic, which consists of three interconnected sub-basins. Their source areas are located in units with contrasting geology and different levels and sources of contamination. The aim of this study is to provide an insight into the provenance of the sediment, including lithogenic elements and anthropogenic pollutants, to investigate the sediment dispersal across the reservoir, and to assess the heavy metal pollution in each basin. The study is based on multi-proxy stratigraphic analysis and geochemistry of sediment cores. There is a considerable gradient in the sediment grain size, brightness, MS and geochemistry, which reflects changing hydrodynamic energy conditions and primary pelagic production of CaCO3. The thickness of sediments generally decreases from proximal to distal parts, but underwater currents can accumulate higher amounts of sediments in distal parts near the thalweg line. Average sedimentation rates vary over a wide range from 0.58cm/yr to 2.33cm/yr. In addition, the petrophysical patterns, concentrations of lithogenic elements and their ratios made it possible to identify two main provenance areas, the Dyje River catchment (upper basin) and the Svratka and Jihlava River catchments (middle and lower basin). Enrichment factors (EF) were used for distinguishing the anthropogenic element contribution from the local background levels. We found moderate Zn and Cu pollution (EF ~2 to 5) in the upper basin and Zn, Cu and Pb (EF ~2 to 4.5) in the middle basin with the peak contamination in the late 1980s, indicating that the two basins have different contamination histories.
Keywords: Reservoirs; Multi-proxy stratigraphic analysis; Enrichment factors; Sediment accumulation rates; Heavy metals